Retrospective evaluation of pericardial catheter placement in the management of pericardial effusion in dogs (2007–2015):18 cases. Issue 4 (22nd June 2019) - Cook, Simon; Cortellini, Stefano; Humm, Karen
Abstract: Objective: To describe the use of pericardial catheters in dogs with pericardial effusion (PE), and detail any associated adverse events. Design: Retrospective study. Setting: University teaching hospital. Animals: Eighteen client‐owned dogs that had pericardial catheters placed for pericardial fluid drainage between May 2007 and January 2015. Interventions: None. Measurements and main results: All pericardial catheters were placed within 5 hours of presentation, usually within 1 hour (median 72.5 min, range 45–300 min). Ten of 18 cases were sedated with butorphanol, and 4 with additional midazolam. Four had pericardial catheters positioned for single drainage only and were immediately removed. The other 14 pericardial catheters remained in situ for a median of 18 hours (range 2–88 h). Ten of the remaining 14 cases were redrained after pericardial catheter placement. The main adverse events reported were new arrhythmias in 6/18 cases, with 4 of these 6 patients being administered anti‐arrhythmic therapy. No infectious or functional complications were reported. Ten patients were discharged, 1 died and 7 were euthanized. Conclusions: Thoracic drainage catheters inserted into the pericardial space via a modified‐Seldinger technique can be positioned in dogs to aid management of PEs. The main associated adverse event is arrhythmia. Minimal sedation is required for placement, and dogs tend not to require postprocedural analgesia. Catheters can remain in situ for repeated drainage, potentially decreasing staffing time requirement and repeat sedation. Their use is associated with a rate of arrhythmia requiring treatment of 22%, compared to that of needle pericardiocentesis alone at 13%. They are easy to position using equipment available in many facilities.